2021
DOI: 10.16875/stem.2021.22.4.27
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of the Fairness of Video Presentation Grading in the Online EFL Classroom

Abstract: This qualitative case study, which employed thematic analysis, explores student perceptions about the fairness of grading video presentations in an online EFL Korean classroom. The study surveyed 145 students about their attitudes towards the fairness of grading for video presentations using three open-ended questions. To better understand the students’ thoughts, they were asked what most affected the fairness of grading live versus video presentations. It found that students believed that the use of video pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…They evaluated the fairness of prediction models via both true positive rate (well-performing students) and true negative rate (students who need help) metrics that represent the equity of opportunity. Copeland (2021) surveyed student attitudes about the grading fairness of video presentations and found that a clear rubric explained before the homework and posted so that students can see and understand improved the perceived fairness of grading. Friedler et al (2008) developed a visualization tool to help teachers explore the relationships of particular students to classes to have fairer assessment.…”
Section: Hybrid Data Analytic Techniquementioning
confidence: 99%
“…They evaluated the fairness of prediction models via both true positive rate (well-performing students) and true negative rate (students who need help) metrics that represent the equity of opportunity. Copeland (2021) surveyed student attitudes about the grading fairness of video presentations and found that a clear rubric explained before the homework and posted so that students can see and understand improved the perceived fairness of grading. Friedler et al (2008) developed a visualization tool to help teachers explore the relationships of particular students to classes to have fairer assessment.…”
Section: Hybrid Data Analytic Techniquementioning
confidence: 99%